Impact of COVID-19 pandemic on blood donation during 1st wave in India: Understanding regular blood donors and non-blood donor’s perspective, attitudes, and practices - Chunchu, Srinivasa Rao; Bala, Sudha; Rajiv Kumar B; Ushasree Ravula (Asian Journal of Medical Sciences, 2022)
Background: COVID-19 is an emerging and rapidly evolving situation globally, and it poses additional burden for emergency health care services especially the transfusion medicine and the need of an hour to safeguard our regular blood donors. Aim and Objectives: The study aims to find out the proportion of COVID-19 infection among blood donors and non-blood donors (NBDs) and to assess their behavioral risk factors that predispose to COVID-19. Materials and Methods: A case-control study was conducted among regular blood donors and non-blood donors at the department of transfusion medicine attached to tertiary care hospital with an objective to find out the proportion of COVID-19 status and the risk factors associated with its occurrence. Results: Total of 834 participants involved in our study. Accordingly, we found the proportion of COVID-19 to be 9% among regular blood donors and 2% among NBDs. A significant association was noted with regular going out, co-morbidities, B positive blood group and perceived stress as the risk factors in regular blood donors. Moreover, among NBDs maintaining social distancing and regular washing of hands/use of sanitizers were significant factors. Conclusions: The novelty of this study helps to remake our policies concerned mainly on the protection of our potentially emergency service providers against COVID-19 infection.